The Influence of Teachers Personality on Students Motivation in Learning English in West Papua: Based on University Students Perspective - Suardi Sahid (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study is to determine how the personality of the teacher affects students' motivation to learn English. This research apllied quantitative research with the total sample was 74 students The research instrument was in the form of questionnaire data which were divided into 2 parts, the first was the respondent's perception of motivation in learning which consists of 15 items. The second was the respondents' perceptions of teachers' personality which consists of 25 items. The data is collected and analyz the data obtained therefore it can be used to answer the problems that have been raised. The verified data was then score using Likert Scale in Microsoft excel. This research are based on a 5-point Likert-type scale including (always), (often), (sometimes), (seldom), and (Never). The information is gathered and analyzed so that it may be utilized to address the issues that have been brought up. In June 2023, data collecting was completed. The findings demonstrated the impact of the teacher's personality on the motivation of the pupils to learn English. This study's key finding is that students are more motivated to learn English when their teachers have positive personalities. The findings of this study provide evidence that teachers should develop their character since it has an impact on student motivation, which improves student accomplishment. Additionally, the personality of the teacher may be used to predict students' willingness to learn English.